Report of the One Hundred and Thirty Sixth Round Table on Transport Economics estimation and evaluation of transport costs. (Round table (Transport Research Centre), 2007)
Cost data for the construction and operation of facilities are essential for the evaluation of infrastructure services supplied by private or public providers. This roundtable examines what data is needed for evaluation; which methods best measure the efficiency of service provision and benchmark providers; how regulatory regimes impact costs; and how regulators can counter the asymmetry of information as well as the incentive for data providers to selectively serve business rather than user interests.--Publisher's description.